2019
DOI: 10.1186/s12935-019-0945-4
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type specific concentration regulation of the basal transcription factor TFIIH in XPBy/y mice model

Abstract: Background The basal transcription/repair factor TFIIH is a ten sub-unit complex essential for RNA polymerase II (RNAP2) transcription initiation and DNA repair. In both these processes TFIIH acts as a DNA helix opener, required for promoter escape of RNAP2 in transcription initiation, and to set the stage for strand incision within the nucleotide excision repair (NER) pathway. Methods We used a knock-in mouse model that we generated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As nuclei in neurons are smaller than those in oocytes, hypodermal and intestinal cells, the TFIIH concentration will also be lower in these cell types. Similar analysis of mouse XPB-YFP fluorescence levels in tissues of XPB-YFP knockin mice also showed that TFIIH levels vary depending on the cell type, which, interestingly, was found to correlate to transcriptional activity in these cells (Donnio et al , 2019). Thus, possibly also in C. elegans TFIIH levels can be used as quantitative biomarker of transcriptional activity.…”
Section: Resultsmentioning
confidence: 65%
“…As nuclei in neurons are smaller than those in oocytes, hypodermal and intestinal cells, the TFIIH concentration will also be lower in these cell types. Similar analysis of mouse XPB-YFP fluorescence levels in tissues of XPB-YFP knockin mice also showed that TFIIH levels vary depending on the cell type, which, interestingly, was found to correlate to transcriptional activity in these cells (Donnio et al , 2019). Thus, possibly also in C. elegans TFIIH levels can be used as quantitative biomarker of transcriptional activity.…”
Section: Resultsmentioning
confidence: 65%
“…It is proposed that FUSE and FIR binding to TFIIH regulates activation-dependent, but not basal MYC expression (82). The level of TFIIH in cells is tightly regulated and correlates with transcriptional activity (84). Thus, we expect that inducible genes that become transcriptionally very active upon stimulation may be more susceptible to XPB degradation than those transcribed at a far lower rate.…”
Section: Downloaded Frommentioning
confidence: 99%